Geographies of knowledge: Science, scale, and spatiality in the Nineteenth century - Mayhew, Robert; Withers, Charles W. J. (Baltimore johns Hopkins University press, 2020)
This collection of essays addresses the role of space in the construction and dissemination of scientific ideas in the nineteenth century. The essays pay particular attention to the role of scale, ranging from the local scale of the Surrey countryside to the global spatiality of the prime meridian.
Keywords: Intellectual life; Intellectual life history